2024
DOI: 10.37978/gulf.v3i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between clinical estimated fetal weights (CEFW) Versus Ultrasonographic estimated fetal weight (UEFW) for co-relation with actual birth weight (ABW) in 3rd Trimester of Pregnancy

Abstract: Background: Accurate prenatal estimation of birth weight is useful in the management of labour and delivery. Objective: To determine the correlation between clinical estimated fetal weight with actual birth weight in 3rd trimester of pregnancy and to determine the correlation between Ultrasonographic fetal weight assessment with actual birth weight in 3rd trimester of pregnancy. Material & Methods: This cross sectional study with non-probability purposive sampling technique was conducted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the study positive correlation was found between the CEFW, UEFW with ABW of the baby concluding that both the clinical estimation ultrasonography estimation showed the feasible and reliable results. Both showed positive correlation with actual birth weight 11. …”
mentioning
confidence: 81%
“…In the study positive correlation was found between the CEFW, UEFW with ABW of the baby concluding that both the clinical estimation ultrasonography estimation showed the feasible and reliable results. Both showed positive correlation with actual birth weight 11. …”
mentioning
confidence: 81%
“…In measuring the height of the uterus, the distance between the upper extremity of the uterus and the upper edge of the symphysis of the pubis was considered to be zero points in the area of the symphysis of the pubis, and the strip meter stretched to the midline of the abdomen to the uterus and somewhere when the uterine peak was touched by the fingers; the height of the womb was measured in cm. To measure the abdominal circumference of the mother, the strip of the membrane in the position of the umbilicus passed through the abdomen and behind the mother, and the corresponding number was recorded in cm [6,9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Also, for the calculation of N, the vaginal examination is performed: when the presenting part is at the minus station, N=13; presenting part was at 'zero' station, N=12; and presenting part was at plus station N=11. In measurements, the examination was done between contractions [6,9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation